2020
DOI: 10.1007/s10902-020-00290-0
|View full text |Cite
|
Sign up to set email alerts
|

The Different Roles of Hedonic and Eudaimonic Motives for Activities in Predicting Functioning and Well-Being Experiences

Abstract: Research on hedonic and eudaimonic orientations has previously focused on their effects on well-being experiences. Very little is known about their associations with functioning. A preliminary objective of the study was to establish the factorial validity of the Hedonic and Eudaimonic Motives for Activities-Revised (HEMA-R) on an Italian sample (N = 461) through a confirmatory factor analysis. The main objective was to study the distinctive patterns of correlates between different types of orientations to well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 25 publications
(43 reference statements)
2
45
0
2
Order By: Relevance
“…For instance, individuals who consider themselves hedonists (high valuing of pleasure) might experience higher subjective well-being because they maintain positive beliefs, i.e., focus on, think, and know more about positive aspects of life. Moreover, hedonists may also initiate actions (hedonism-related activities) that promote positive hedonic outcomes (e.g., engaging in more enjoyable leisure activities) (Giuntoli et al, 2020;Huta & Ryan, 2010). Such behaviors might have relatively little impact on eudaimonic well-being.…”
Section: Value-related Behavior and Well-beingmentioning
confidence: 99%
“…For instance, individuals who consider themselves hedonists (high valuing of pleasure) might experience higher subjective well-being because they maintain positive beliefs, i.e., focus on, think, and know more about positive aspects of life. Moreover, hedonists may also initiate actions (hedonism-related activities) that promote positive hedonic outcomes (e.g., engaging in more enjoyable leisure activities) (Giuntoli et al, 2020;Huta & Ryan, 2010). Such behaviors might have relatively little impact on eudaimonic well-being.…”
Section: Value-related Behavior and Well-beingmentioning
confidence: 99%
“…Previous studies have attempted to investigate this question. For instance, researchers divided the hedonic orientation into the pleasure orientation and the relaxation orientation and found that the pleasure orientation was generally beneficial to individual well-being, whereas the relaxation orientation had a neutral or even detrimental effect [ 7 , 8 ]. However, other studies suggested that the types of hedonic orientation are indistinguishable from one another [ 5 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, high levels of hedonic orientation were related with low levels of grit and investment in learning, which thereby led to poor academic achievement [ 14 , 26 , 27 ]. A hedonic orientation was also related with dysfunctional coping strategies (e.g., addictive behavior), which, in turn, further harmed well-being [ 7 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…This was similar to Zeng and Chen [ 26 ]. These may suggest that pursuing eudaimonia promotes better well-being than pursuing hedonia, eudaimonia and hedonia may foster well-being in different ways [ 14 ]. Second, hedonic and eudaimonic motives were both positively related to social support, and there was no significant difference between them, which suggests that hedonic and eudaimonic motives play an equally important role in social support.…”
Section: Discussionmentioning
confidence: 99%
“…Hedonic motives are defined as seeking pleasure and comfort, while eudaimonic motives refer to people seeking to try their best to use and develop themselves [ 9 ]. Through the years, researchers found that the eudaimonic and hedonic motives exhibited beneficial effects on a wide range of positive outcomes such as academic achievement, emotion regulation, coping strategies and well-being [ 12 , 13 , 14 ]. Thus, measuring and studying hedonic and eudaimonic motives is a vital and necessary topic.…”
Section: Introductionmentioning
confidence: 99%